School Environmental Cleanliness Counseling to Improve Knowledge of Hermon Timika Vocational School Students - Nurwirhanuddin Nurwirhanuddin; Maria Letisia; Habibi Sutirta; Herwin Herwin; Ayu Ayu (Abdi Masyarakat, 2026)
Health education aims to change or influence human behavior individually, in groups, or in society, to enable them to be more independent in achieving healthy living goals. In this health education, a method is needed so that the message can be delivered as expected. The delivery method in this education is by using lectures, videos, and actions towards environmental cleanliness. With this activity, students are expected to be able to increase their knowledge of school environmental cleanliness such as disposing of trash in its place, being able to differentiate organic and inorganic waste, not scribbling on walls and tables, and consciously wanting to work together to clean the yard and classroom. The implementation of community service requires cooperation from various parties so that health education can be carried out not only once, but regularly to monitor the development of students' knowledge about environmental cleanliness in schools. In addition to lectures, videos and actions, the implementation or delivery of health education can also use educational games as media because with games, students can more easily understand, students also do not experience boredom in the delivery of the material.